MODERN CLINICAL AND MORPHOLOGICAL APPROACHES TO THE TREATMENT OF STOMACH CANCER AT AN EARLY STAGE - Nurov Jamshid Raxmatovich (Web of Journals Publishing, 2025)
The article presents the results of histological examination of early gastric cancer removed by endoscopic submucosal dissection. The algorithm of morphological research is given: methods of histological, histochemical and immunohistochemical processing of tissue samples, the sequence of morphological analysis with the conclusion and conclusions about the effectiveness of endoscopic surgery is analyzed.
Keywords: Early gastric cancer, clinical and morphological examination, endoscopic submucosal resection.